PEMBERDAYAAN MASYARAKAT DESA RONGDALEM KECAMATAN OMBEN KABUPATEN SAMPANG SEBAGAI UPAYA MEWUJUDKAN DESA BERKUALITAS - Muryanto, Dwi; Nuada, I Wayan; Amiq, Bachrul (LPPM Universitas PGRI Adi Buana Surabaya, 2019)
Rong Dalem Village in Omben District, Sampang is a Government that implements community service programs in solving social and environmental problems in its area. Important issues in the village are lack of awareness of education, lack of health facilities and infrastructure, lack of initiative and creativity of the community in utilizing the potential of the village and its environment, and knowledge in finding solutions to meet the needs of clean water. For the problemof education, there are still many people who only go to education only to the level of elementary school. Even though they have the financial capacity, the community is more oriented to education in Islamic boarding schools and looking for work than schools. For health problems, the public does not understand the conditions of personal and family health and the lack of health facilities and infrastructure. For the problem of creativity, people are still unable to process and develop existing crops such as peanuts, siwalan trees, tubers and others. The community is only more interested in expanding the potential of tobacco plants alone. As for the problem of meeting clean water needs, during the dry season water resources are difficult, but in the rainy season the water is not absorbed by the soil. The purpose of this activity is: to give insight to the community to be aware of education, be aware of their potential and environment so that they are motivated to build, develop, and empower society and the environment. The method of implementing this activity is by conducting counseling and training. The results of this activity are that the community of Rong Dalem are aware of and understand the importance of education, the development of their potential and environment, and are able to manage water resources by practicing the way of making drainage channels and water tanks.